TREN PENELITIAN STRUKTUR TEKTONIK INDONESIA 2001-2020: SEBUAH PENDEKATAN BIBLIOMETRIK - Rulina Rachmawati (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
This paper aims to analyze the research trend of publications of Indonesia’s tectonic settings, which consist of the growth of publication numbers, the main research topics (including the used research methods and the most researched geographic area), the growth of the research topics, the source of publications, the institutional and country affiliations, and the collaboration between national and international researchers. A bibliometric method was used to analyze publications indexed by Scopus database from 2001 to 2020. VosViewer software was used to visualize the keyword map and to find the main research topics, the methods and the geography of the research. The growth of the research topics was analyzed manually through a content analysis and classification into the main research topics. The publication sources, the affiliations and the collaborations were analyzed statistic-descriptively. The result shows that there is an increase on the number of Indonesia’s tectonic settings publications within the last decade. There are four main research topics: (1) tectonic structure on subduction or fault zone in relation to seismic activities or tectonic slips (method: tomography and GPS; locus: Sumatera and Central Java); (2) physical processes beneath the magma plumbing systems and magma evolution (magma differentiation) (method: geochemistry, petrology, isotopic ratio, petrography analysis; locus: Java (East and Central Java, especially Mount Merapi); (3) tectonic structure evolution caused by arc-continent collision (method: stratigraphy, biostratigraphy, geochronology analysis; locus: Banda arc, Lesser Sunda Islands and Sulawesi); (4) magmatic processes or sedimentology in relation to crustal of the subduction zone (method: isotopic composition dan igneous geochemistry analysis; locus: West Java). Most publications are published on Geophysical Journal International, but Gondwana Research shows a higher citation score. Bandung Institute of Technology is the most productive institution, while Indonesia is the most productive publication country followed by the UK and Australia. Most publications are resulted from collaborations of national and international researchers, however the number of national researchers as the first writer is relatively low (22%).